ASPECTOS IMUNOLÓGICOS DO LEITE MATERNO - Oliveira, Lázaro Heleno Santos de; Bispo, Joicielly França; Bispo, Joicielly França; Santos, Clécia Almeida; Santos, Clécia Almeida; Oliveira, Joyce Stephane Ferreira Albuquerque de; Oliveira, Joyce Stephane Ferreira Albuquerque de; Souza, Wbiratan de Lima; Souza, Wbiratan de Lima (Gep News, 2019)
Trabalho apresentado no I MASMI